Fatty acid composition of lamb meat from Italian and German local breeds - Gonzales-Barron, Ursula (2018)
The aim of this study was to evaluate and compare the quality characteristics, chemical composition and lipid profile of lamb meat from Italian (Biellese and Sambucana) and German (Texel-Merino-Blackhead-Charollais [TMBC]) breeds reared in extensive and semi-extensive production systems. Meat samples from 89 animals were analysed. The meat of the lambs from semi-intensively reared Biellese, and extensively reared Sambucana and TMBC breeds produced lean meat, with slightly higher intramuscular fat content in TMBC. The latter also produced meat of darker colour (P lt 0.05) and higher protein content (P lt 0.05). The meat of Sambucana lambs presented the lowest total cholesterol content (P lt 0.05). The fatty acid profile of the meat showed a clear advantage of both extensively reared breeds, which had substantially lower proportion of saturated but higher of polyunsaturated fatty acids, particularly n-3 (P lt 0.05). The beneficial effect of the extensive rearing conditions was associated with lower n-6/n3 ratio, and atherogenic and thrombogenic indices, thereby suggesting that production system can be used successfully to modify the fatty acid profile to achieve a positive effect for the human health.